성인 남성에서 체질량지수로 분류한 비만 유형에 따른 혈청 감마 글루타밀 전이효소와 혈청 요산농도의 차이 비교 - 신경아; Kyung A Shin (Korean journal of clinical laboratory science, 2019)
본 연구는 성인 남성을 대상으로 체질량지수로 분류한 비만유형에 따른 혈청 GGT와 요산농도의 차이와 관련성을 확인하고자 하였다. 2017년 1월부터 2018년 8월까지 경기지역 종합병원의 건강검진센터를 내원하여 건강검진을 실시한 20세 이상 성인 남성 14,283명을 대상으로 하였다. 비만 기준은 아시아-태평양지역 기준을 적용하였으며, 복부비만은 남성의 허리둘레 90 cm이상을 기준치로 정의하였다. 남성 대상자의 혈청 요산농도 상승은 7.0 mg/dL 이상, 혈청 GGT 상승은 56 IU/L 이상으로 정의하였다. 본 연구결과 혈청 GGT와 요산농도는 정상체중군보다 과체중과 비만군에서 높았으며, 비만군에서는 복부비만을 동반한 경우 혈청 GGT (53.26±49.67 IU/L vs 67.66±60.16 IU/L) 및 요산농도(6.22±1.26 mg/dL vs 6.38±1.40mg/dL)가 유의하게 높았다. 그러나 저체중군과는 차이가 없었다. 또한 과체중과 비만군은 정상체중군보다 혈청 GGT 상승과 고요산혈증의 위험이 높게 나타났으나, 저체중은 혈청 GGT 상승과 고요산혈증에 영향을 미치지 않는 것으로 나타났다. 따라서 성인 남성의 과체중 및 비만을 평가하는데 혈청 GGT와 요산이 유용하다고 판단된다. This study examined the relationship between the serum GGT (gamma-glutamyl transferase) and uric acid level in obese male adults. A total of 14,283 adult males aged 20 years or more, who visited the health examination center of Gyeonggi Regional General Hospital from January 2017 to August 2018 and underwent a physical examination, were enrolled in this study. The obesity criteria were defined by the Asia-Pacific regional standards. Abdominal obesity was defined as a male waist circumference of more than 90 cm. An increase in the serum uric acid and serum CGT levels of the male subjects was defined as 7.0 mg/dL or more and 56 IU/L or more, respectively. The results showed that the serum GGT and uric acid levels were higher in the overweight and obese groups than in the normal weight group. In the obese group, the serum GGT and uric acid were significantly higher in the patients with abdominal obesity. On the other hand, there was no difference compared to the low body weight group. The overweight and obesity groups showed a higher risk of elevated serum GGT and hyperuricemia than the normal weight group, but a low body weight did not affect the serum GGT elevation and hyperuricemia. Overall, the serum GGT and uric acid levels are useful for evaluating overweight and obesity in adult males.